PENGARUH KOMPLEKSITAS EKONOMI TERHADAP EMISI KARBON DIOKSIDA DI NEGARA G20: ENVIRONMENTAL KUZNETS CURVE (EKC) - Al Qodri, Muhammad Iqbal; Widyastutik, Widyastutik; Rachbini, Eisha Maghfiruha (LPPM - STIE SAKTI ALAM KERINCI, 2024)
Economic growth not only increases the size of the economy, but also the variety of technology used in production, which are captured by the Economic Complexity Index (ECI) approach. Many countries seek to increase its economic complexity through the industrial sector to accelerate economic growth. On the other hand, energy sources from coal and petroleu so resulting in high emissions. The objective of this study is to analyze whether economic complexity can reduce emissions by using the Environmental Kuznets Curve (EKC) approach. The research method used are Fully Modified OLS (FMOLS) and Dynamic OLS (DOLS) for 18 selected G20 countries from 1995-2020. This study found that economic complexity reduced carbon dioxide emissions after passing the turning point in the long run, in the case of both developed and developing G20 countries. In addition, for developed G20 countries that FDI and renewable energy contributed to reduce emissions. However, for developing G20 countries that FDI and renewable energy increased carbon dioxide emissions. This study suggested that low emissions technology innovation need to be optimized through FDI, for developed G20 countries. Furthermore, for developing G20 countries, strengthening G20 cooperation for energy transition, particularly in low emission investment financing, is needed.